Feature analysis of android-based holy Quran applications - Kamal Z., Zamli; Rozlina, Mohamed; Rohani, Abu Bakar; Alsewari, Abdulrahman A. (IEEE, 2015)
Given the popularity of mobile devices and the corresponding Android Operating System, many interactive Islamic applications have started to emerge. Concerning the Holy Quran applications, users are often baffled with many choices of implementations. In order to help user makes informed decisions, this paper describes the survey and analysis of existing Android based interactive Holy Quran software applications for mobile devices. In doing so, this paper proposes a set of feature analysis criteria to form the guidelines and requirements for future development of the interactive Holy Quran software applications.